Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/ep.13125
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of greenhouse gas (GHG) emissions from stainless steel production in China using two evaluation approaches

Abstract: In recent years, global warming has become a growing concern around the world, and greenhouse gases (GHG) are its major cause. In the current study, the GHG emissions from stainless steel production in Mainland China was evaluated based on two approaches. One (i.e., Approach I) was based on the data, which were collected from a life cycle inventory database (Ecoinvent). The second evaluation (i.e., Approach II) was performed according to the 2015 comprehensive energy consumption data of the Chinese stainless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The study examined the load distribution factor and neutral axis position of two steel box girder bridges to extend the service life of the bridges and the results showed that extending the service life will reduce the use of construction materials, which will decrease the GHG emissions significantly. Generally, steel production is one of the largest total environmental effects of all industrial operations and is one of the major contributors to GHG emissions [ 58 ]. Moreover, in 2014 steel accounted for 6.6% of global GHG emissions and 8% of energy related emissions [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study examined the load distribution factor and neutral axis position of two steel box girder bridges to extend the service life of the bridges and the results showed that extending the service life will reduce the use of construction materials, which will decrease the GHG emissions significantly. Generally, steel production is one of the largest total environmental effects of all industrial operations and is one of the major contributors to GHG emissions [ 58 ]. Moreover, in 2014 steel accounted for 6.6% of global GHG emissions and 8% of energy related emissions [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Life-cycle analysis (LCA; determination of the carbon footprint from production through disposal) for both materials is difficult to determine. Stainless steel has a large global carbon footprint because of its requirements of mining, heating, off-gassing, and transporting 29 . Suture anchors are frequently made of PEEK (polyetheretherketone), a biologically inert plastic-like material 30 .…”
Section: Carbonmentioning
confidence: 99%